Neonatal Mortality in Yogyakarta Rural Areas - Achmad Surjono (Indonesian Pediatric Society, 1988)
The outcome of neonatal care was studied in three subdistricts rural areas in Yogyakarta Province with a total population of 112075 people. For data collection all pregnancies and deliveries between May 1983 -April 1984 were registered and visited twice during pregnancy, on delivery, 5 days and one month afterwards by trained health cadres. There were 1819 singleton liveborn infants with a neonatal mortality rate of 25.3 o/oo, in which 82.6% of the deaths occurred in the early neonatal period. An amount of 91.5% of the women delivered in their own house and 83.9% were assisted by a traditional birth attendant either trained or untrained. There was still 27.1% of pregnancies which never got any antenatal care. The coverage of tetanus immunization was 75.2% with 1.1 o/oo incidence of tetanus. The incidence of low birth weight infants was 8.1%, of which 19. 7% died before one month of age, I representing 63% of neonatal mortality. The causes of neonatal deaths were as follows: birth asphyxia and hypoxia 56.5%, prematurity/low birth weight 13%, infection/sepsis 13%, diarrhea 8. 7%, tetanus neonatorum 4.4% and others/unknown 4.4%. In rural areas, traditional birth attendants play a key role on assisting labour and taking care of the mothers as well as their newborns up to one month of age. Improvement of health service delivery at all levels of the health care system which includes the traditional birth attendants is needed especially concerning resuscitation of the newborns and the problems of low birthweights.